TINGKAT KARAKTERISTIK (Umur, Paritas, Pendidikan) IBU HAMIL TENTANG KEJADIAN KEHAMILAN RESIKO TINGGI - Arimina Hartati Pontoh (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2018)
High-risk pregnancy is pregnancy with a state of normal deviation that can directly cause morbidity and death for both mother and baby (Dinkes jatim, 2010). The high risk pregnancy tolerance rate according to the East Java Health Office in 2010 is 20%. In the last 3 years the incidence of high-risk pregnancies in the Polindes of Sidorejo Village in 2014-2016 has increased, ie from 2014 to 2015 it increased by 3.55%. While from 2015 to 2016 it decreased by 2.45%, but this is still above the tolerance level. The purpose of this study was to describe the incidence of high-risk pregnancies based on age, parity and education. Method: In this study the descriptive method was used in which the sampling was done by total sampling with a sample size of 194 people. The research instrument by utilizing secondary data by looking at the pregnancy register data in the Polindes of Sidorejo Village was then processed using frequency tabulation and cross tabulation. Results: Based on the results of the study it was found that the incidence of high-risk pregnancies was 71 people (36.60%). At the age of the majority of high risk pregnancies were found at age ? 35 years as many as 39 people (92.86%). Parity was found that the majority of high risk pregnancies occurred in pregnant women with grandemultipara parity of 39 people (70.91%). Whereas in education the majority of high risk pregnancies occur in mothers with primary education as many as 40 people (68.97%) Discussion: From the results of the study it can be concluded that the majority of high-risk pregnancies occur at ? 35 years old, grandemultipara and have basic education. Therefore, to reduce the incidence of high-risk pregnancies, an examination is required early in pregnancy, so that it can be detected if there are complications and can immediately treat it.